O uso de chatbots no atendimento de clientes de revenda por catálogo - GADELHA, Igor Bruno Liz (Universidade Federal do Pará, 2020)
Increasingly, the presence of technologies that use artificial intelligence techniques are present in our daily lives, the development of systems and machines increasingly capable of performing tasks once performed by humans is increasingly present. In the corpotarivo sector, customer service through chatbots is already a reality and it becomes more and more common everyday. The use of bots in the customer service, besides allowing the reduction of costs, makes possible the standardization of the processes of attendance and automation of repetitive occurrences. The study environment of this work was the service and marketing sector of a company specialized in reselling products through catalogs. Problems were identified in relation to customer response time, repetitive attendance and the occurrence of out-of-hours services, in addition to the increase in costs with attendance due to the growth of the business. The objective of this research was to implement a chatbot capable of assisting customer service, reducing the repetitive demands to the human attendants of the sector. To guarantee the alignment of chatbot customer service demands, from the pareto method, the identification and classification of the occurrences of the sector was carried out, direccionarando in the construction of a corpus of language and models of natural language processing components using Rasa NLU and Rasa Core.